Compressed Air Engine Analysis - Mukhtar, Sarban; Majadi, Himayatullah; Abdullah, Milad Ahmad (Journal of Natural Sciences – Kabul University, 2024)
This paper explores practical solutions for using alternative sources like compressed air instead of standard fuels in internal combustion engines. The study aims to address the excessive use of natural resources and fuel materials by investigating the feasibility of operating internal combustion engines with compressed air. The research focuses on designing and converting a four-stroke petrol engine to operate on compressed air. Scientific research and analyses are based on laboratory experiments and the evaluation of relevant results. Key aspects include analyzing and modifying cam lobes in internal combustion engines, which are essential for converting combustion-based systems to compressed air operation. Compressed air as a fuel alternative can improve engine efficiency, enhance environmental quality, and reduce costs. Additionally, integrating intelligent control systems can further optimize performance and efficiency.